Growth Performances of Shibot Fish (Tor grypus) Fry Fed with Diets Containing Different Protein Levels - Suat Dikel; Ilgın Özşahinoğlu; Mustafa Öz; İbrahim Demirkale (Turkish Journal of Agriculture: Food Science and Technology)
In the study, the growth performances of the Shibot fish (Tor grypus) with an average weight of 2.38 g were evaluated by feeding them with 3 different protein-containing feeds for 45 days. In order to create these evaluations, the experimental groups were designed as G1 (33%), G2 (37%) and G3 (41%) fed with different protein levels. Effects on body weight gain (BWG), Feed conversion rate (FCR), Specific growth rate (SGR), Survival rate, Economic conversion rate (ECR) and Economic profit index (EPI) as growth parameters has been researched. At the end of the study, the offspring reached a weight of 3.42±0.16 g, 4.17±0.06 g and 4.50±0.02 g, respectively. G3 and G2 group individuals showed similar performance in terms of end-trial FCR, EPI and ECR.